Kinetic studies on the synthesis of fuel additives from glycerol using CeO2–ZrO2 metal oxide catalyst - Rajeswari M. Kulkarni; Pradima J. Britto; Archna Narula; Syed Saqline; Deeksha Anand; C. Bhagyalakshmi; R. Nidhi Herle (Biofuel Research Journal, 2020)
Highly stable and active CeO2-ZrO2 metal oxide catalyst was synthesized via the combustion method and was further functionalized with sulphate (SO42-) groups. The morphology, surface functionalities, and composition of the metal oxide catalyst were determined by scanning electron microscopy, N2 adsorption and desorption measurement, X-ray diffraction, and Fourier transform infrared spectroscopy. The synthesized catalyst was used for esterification of glycerol with acetic acid. Effects of the process parameters including acetic acid to glycerol molar ratios (3-20), catalyst loadings (1-9 wt.%) and reaction temperatures (70–110°C) on the glycerol conversion and glycerol acetates selectivity were studied. Excellent catalytic activity was observed by using the sulphated metal oxide catalyst resulting in a glycerol conversion as high as 99.12%. The selectivity towards the di and triacetin (fuel additive) formed stood at 57.28% and 21.26% respectively. The reaction rate constants and activation energies were also estimated using a Quasi-Newton algorithm, namely Broyden’s method and Arrhenius equations at 80-110℃. The calculated values were in accordance with the experimental values which confirmed the model. Finally, the developed catalyst could be reused for three consecutive cycle without major loss of its activity. Overall, the findings presented here could be instrumental to drive future research and commercialization efforts directed toward biodiesel glycerol valorisation into fuel additives.